Role and regulatory mechanism of microRNA mediated neuroinflammation in neuronal system diseases - Zhang, Jingdan; Li, Ao; Gu, Runze; Tong, Yueyang; Cheng, Jinbo (Frontiers in Immunology, 2023)
MicroRNAs (miRNAs) are small non-coding RNAs with the unique ability to degrade or block specific RNAs and regulate many cellular processes. Neuroinflammation plays the pivotal role in the occurrence and development of multiple central nervous system (CNS) diseases. The ability of miRNAs to enhance or restrict neuroinflammatory signaling pathways in CNS diseases is an emerging and important research area, including neurodegenerative diseases, stroke, and traumatic brain injury (TBI). In this review, we summarize the roles and regulatory mechanisms of recently identified miRNAs involved in neuroinflammation-mediated CNS diseases, aiming to explore and provide a better understanding and direction for the treatment of CNS diseases.